UMPSA s Bachelor of Project Management programme obtains international accreditation from PMI GAC for 5 years - Nurhaizan, Mohd Zainudin (UMPSA, 2025)
GAMBANG, 16 January 2025 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) has made history with its Bachelor of Project Management with Honours Programme, under the Faculty of Industrial Management (FPI), receiving international recognition.